2010
DOI: 10.1016/j.visres.2010.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spatial proximity and collinearity on contour integration in adults and children

Abstract: We tested adults and children aged 7 and 14 on the ability to integrate contour elements across variations in the collinearity of the target elements, their spatial proximity, and the relative spacing of the target elements to the background noise elements (Delta). When collinearity was high, the strength of integration for adults was largely independent of spatial proximity and varied only with Delta. It was only when collinearity was less reliable because the orientation of the elements was randomly jittered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 33 publications
9
52
1
Order By: Relevance
“…The 8-year-olds required a much greater mismatch in the direction of gaze than the adults to reliably detect the mismatch. This is consistent with findings that children in this age range are less sensitive than adults in making other judgments about spatial relations in both faces and non-face stimuli (Baudouin et al, 2010;Hadad, Maurer, & Lewis, 2010a;Hadad, Maurer, & Lewis, 2010b).…”
Section: Discussionsupporting
confidence: 91%
“…The 8-year-olds required a much greater mismatch in the direction of gaze than the adults to reliably detect the mismatch. This is consistent with findings that children in this age range are less sensitive than adults in making other judgments about spatial relations in both faces and non-face stimuli (Baudouin et al, 2010;Hadad, Maurer, & Lewis, 2010a;Hadad, Maurer, & Lewis, 2010b).…”
Section: Discussionsupporting
confidence: 91%
“…The effect shown here of contour geometry on interpolation in young childhood is in agreement with the effect of spatial distances shown in contour integration studies (Kovacs et al, 1999;Hadad et al 2010aHadad et al , 2010b. Both interpolation in the cases of subjective and occluded contours and integration of fragmented elements into a contour is critically restricted during childhood by the spatial distance over which this perceptual process is employed, with both cases of contour perception extending over nearly the same spatial distances.…”
Section: Discussionsupporting
confidence: 86%
“…This local mechanism is strongly governed by contour relatability, such that contours that are smooth and monotonic, and at their endpoints match the slopes of real contours, are more readily interpolated (Kellman & Shipley, 1991). Given this critical role of relatability, some tolerance around collinearity early in life, with gradual decrease in this tolerance as perceptual experience accrues (Hadad et al, 2010b), might underlie the agerelated changes in interpretation observed here.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations